Biophysical Approach to Chronic Kidney Disease Management in Older Patients. Issue 1 (2016) - Foletti, Alberto; Cozzolino, Mario
Background: Chronic kidney disease (CKD) and its clinical progression are a critical issue in an aging population. Therefore, strategies aimed at preventing and managing the decline of renal function are warranted. Recent evidence has provided encouraging results for the improvement of renal function achieved through an integrated biophysical approach, but prospective studies on the clinical efficacy of this strategy are still lacking. This was an open-label prospective pilot study to investigate the effect of electromagnetic information transfer through the aqueous system on kidney function of older patients affected by stage 1 or 2 CKD. Methods: Patients received biophysical therapy every 3 months over a 1-year period. Estimated glomerular filtration rate (eGFR) values were calculated using the CKD-Epidemiology Collaboration formula, and were recorded at baseline and at the end of treatment. Overall, 58 patients (mean age 74.8 ± 3.7 years) were included in the study. Results: At baseline, mean eGFR was 64.6 ± 15.5 mL/min, and it significantly increased to 69.9 ± 15.8 mL/min after 1 year (+5.2 ± 10 mL/min, p<0.0002). The same trend was observed among men (+5.7 ± 10.2 mL/min, p<0.0064) and women (+4.7 ± 9.9 mL/min, p<0.014). When results were analyzed by sex, no difference was found between the 2 groups. Conclusions: Although further and larger prospective studies are needed, our findings suggest that an integrated biophysical approach may be feasible in the management of older patients with early-stage CKD, to reduce and prevent the decline of renal function due to aging or comorbidities.